Dysphagia related quality of life and its association with cognitive function and sociodemographic factors among older stroke patients in Amman, Jordan - Rjoob, Mohammad Abdel-Halim M Al (2023)
Dysphagia is a disorder that compromises the movement of food and liquids from the mouth to the stomach. It is a frequent disorder in stroke patients, affecting 50% to 80% of them. Dysphagia and its complications negatively impact the emotional, functional, and physical aspects of stroke patients. Moreover, cognitive impairment is one of the most common disabilities after a stroke, affecting 20% to 80% of stroke survivors. Previous studies have shown that the severity of dysphagia increases with the severity of cognitive dysfunction. However, the correlation between cognitive function and the handicapping effect of dysphagia on emotional, functional, and physical aspects of quality of life (QOL) in stroke patients is still unknown. Thus, this study aimed to investigate the correlation between cognitive function and the handicapping effect of dysphagia on emotional, functional, and physical aspects of QOL in stroke patients. A total of 31 stroke patients with dysphagia participated in this cross-sectional study. The Arabic version of the Montreal Cognitive Assessment (MoCA) was used to assess patients' cognitive function. Furthermore, the Arabic version of the Dysphagia Handicap Index (DHI) was used to assess the emotional, functional, and physical effects of dysphagia in stroke patients. Most of the patients (61.3%) were male, and the majority (67.7%) were between 60-70 years old. The findings showed that 35.5% of the patients had impaired cognitive function, and the mean ± SD of the DHI total score was 53.5 ± 9.6. Moreover, the results indicated that there was a statistically significant difference in the means of the physical subscale (p=0.003), emotional subscale (p=0.020), and the DHI total score (p=0.005) between groups with different onsets of dysphagia, indicating that the handicapping effect of dysphagia on the physical and emotional aspects, and overall QOL decreases with time following a stroke. Additionally, the findings showed a weak negative correlation between cognitive function (MoCA total score) and the handicapping effect of dysphagia on the physical subscale (r = -0.418, p = 0.019) and the DHI total score (r = -0.368, p = 0.042). Our findings suggest that dysphagia negatively affects QOL aspects, and cognitive function may have a role in the severity of the handicapping effect of dysphagia on the QOL aspects. Thus, looking into the affected QOL aspects secondary to the debilitating dysphagia and the associated cognitive function will be very helpful for dysphagia management and rehabilitation.